Dampak Pola Asuh Otoriter terhadap Keterampilan Pengambilan Keputusan pada Anak: Sebuah Systematic Literature Review - Sunarsih, Nemi; Hartanto, Dody; Martaningsih, Sri Tutur; Saputra, Wahyu Nanda Eka; Setyowati, Aprilia (Universitas Muhammadiyah Metro, 2026)
Decision-making skills are essential life skills that need to be developed from an early age, as they contribute to children’s independence, self-confidence, and critical thinking abilities. The development of these skills is strongly influenced by parenting styles, particularly strict parents or authoritarian parenting, which is characterized by high control and limited child participation. This study aims to comprehensively examine children’s decision-making skills from the perspective of strict parents using a Systematic Literature Review (SLR) approach. Relevant peer-reviewed articles published over the last ten years were systematically selected and analyzed following the PRISMA guidelines and thematic synthesis techniques. The findings indicate that authoritarian parenting tends to have a negative impact on children’s decision-making skills, particularly in terms of autonomy, emotional regulation, and self-confidence. Although parental strictness may provide behavioral structure, its positive effects are limited unless accompanied by open communication and emotional support. This study highlights the importance of balancing parental control and autonomy support to foster optimal development of children’s decision-making skills across developmental stages